Penerapan Metode Economic Order Quantity (EOQ) dalam Pengendalian Persediaan Bahan Baku Kayu pada UD. Khairun Jaya - Azlina Azmi Siahaan; Hendra Harmain; Isnaini Harahap (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
This study aims to analyze raw material inventory control at UD. Khairun Jaya using the Economic Order Quantity (EOQ) method. Inefficient inventory management has led to high ordering frequency and inventory costs. This research employs a descriptive quantitative approach using EOQ and Total Inventory Cost (TIC) analysis. Data were collected through observation, interviews, and documentation related to raw material usage, ordering costs, and holding costs. The results indicate that the optimal order quantity based on EOQ is 5,947 inches with an ordering frequency of 4 times per year. The total inventory cost using EOQ is Rp1,483,677, which is lower than the company’s policy cost of Rp3,964,643. Therefore, the implementation of EOQ proves to be effective in improving cost efficiency and assisting the company in determining optimal inventory policies. The Economic Order Quantity (EOQ) method is considered a suitable reference for raw material inventory management, as it can improve operational efficiency while ensuring the continuity of the production process.